Increasing the Geranoil Content of Palmarosa Oil by Chemical Methods - Mullakoya C P (Department of Soil Science and Agricultural Chemistry, Horticulture College, 1997)
Palmarosa, Cymbopogon martinii (Stampf) var. motia is an important essential oil crop grown commercially in various states of peninsular India. Palmarosa oil finds extensive use in flavouring, cosmetics and toiletry. The oil is valued for the principal constituent geraniol, present in the oil to the extent of 75-82%. Besides being a high grade perfume, geraniol is the starting material for a number of synthetic aroma chemicals. Next to geraniol, the most abundant chemical component of the oil is geranyl esters, predominantly geranyl acetate. Most oils contain about 2 - 12% geranyl acetate. Several factors like the genotype, season, harvest stage, method of oil extraction etc. influence the ratio of geraniol to geranyl acetate in the oil and it is found that a reciprocal relationship exists between the geraniol and geranyl acetate content of the oil. At most times, the geraniol content of palmarosa oil produced by cultivators fall short of requirements of the user industry. The availability of an inexpensive and efficient method of hydrolytic conversion of geranyl acetate to geraniol will facilitate the farmer to undertake an on-farm quality upgradation of his product which will fetch him better price. A laboratory investigation was carried out at the Aromatic and Medicinal Plants Research Station, Odakkali, Kerala during 1994-96 to develop a method for upgrading the quality of palmarosa oil by the conversion of geranyl acetate in the oil to geraniol. Four treatments were tried for the hydrolysis of geranyl acetate, with essential oil of palmarosa type ODP-3 as the test material viz., methanolic sodium hydroxide, methanolic sodium carbonate, ammonia and aqueous sodium hydroxide. Mixing of essential oil with 5% methanolic NaOH reagent in the ratio of 1 : 4 and keeping undisturbed at ambient conditions for 30 min were the optimum conditions for the complete hydrolysis of geranyl acetate in the oil. The product of reaction analysed 90.5% geraniol and the process yielded geraniol to the extent of 78.74% of the oil